2012
DOI: 10.3171/2011.4.jns102155
|View full text |Cite
|
Sign up to set email alerts
|

A new transvenous approach to the carotid-cavernous sinus via the inferior petrooccipital vein

Abstract: The transvenous approach to the cavernous sinus via the IPOV should be considered as an alternative in cases when use of the IPS is precluded by an anatomical problem and there are no other suitable venous approach routes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Another beak-like structure was identified adjacently but with the reference to the bone, this was found to be an extracranial structure being possibly the inferior petro-occipital vein. 5,6 In this specific case, the venography obtained by the 2D method could not show the precise location of the IPS-IJV junction as they overlap. Furthermore, the common opening of the IPS and the inferior petro-occipital vein could only be identified precisely using the 3D images.…”
Section: Materials Methods and Resultsmentioning
confidence: 96%
“…Another beak-like structure was identified adjacently but with the reference to the bone, this was found to be an extracranial structure being possibly the inferior petro-occipital vein. 5,6 In this specific case, the venography obtained by the 2D method could not show the precise location of the IPS-IJV junction as they overlap. Furthermore, the common opening of the IPS and the inferior petro-occipital vein could only be identified precisely using the 3D images.…”
Section: Materials Methods and Resultsmentioning
confidence: 96%
“…Mitsuhashi et al 25 demonstrated the IPS drainage directly into the vertebral plexus with no connection to the IJV in 3/83 sides (3.6%) and the IPS was absent in 14/ 83 sides (16.9%). In our series also, absence of connection with the IJV was noted in one (10%) of 10 venous sampling procedures from the cavernous sinus in five patients 23 .…”
Section: Indications and Contraindications Of Each Proceduresmentioning
confidence: 89%
“…In our series, with two (cases 1 and 2) (11%) of 18 dural CCF patients the conventional venous approach via the IPS failed 23 . These two patients were referred to our institute more than 1 year after development of initial symptoms, which may have contributed to obstruction of the IPS with an organized old thrombus.…”
Section: Indications and Contraindications Of Each Proceduresmentioning
confidence: 99%
See 2 more Smart Citations